PROPOSED METHOD FOR GROUNDWATER VULNERABILITY MAPPING IN CARBONATE (KARSTIC) AQUIFERS: THE COP METHOD - Vías J.M.; Andreo B.; Perles M.J.; Carrasco F.; Vadillo I.; Jiménez P. (My University, 2006)
The ‘COP method’ has been developed for the assessment of intrinsic vulnerability of carbonate aquifers in the frame of the European COST Action 620. This method uses the properties of overlying layers above the water table (O factor), the concentration of flow (C factor) and precipitation (P factor) over the aquifer, as the parameters to assess the intrinsic vulnerability of groundwater. This method considers karst characteristics, such as the presence of swallow holes (C factor) and their catchment areas as well as karstic landforms, as factors which decrease the natural protection provided by overlying layers (O factor). The P factor allows for consideration of the spatial and temporal variability of precipitation, which is considered the transport agent of contamination. Two carbonate aquifers in the South of Spain, Sierra de Líbar (a conduit flow system) and Torremolinos (a diffuse flow system), have been selected for the application and validation of the method and the results have been compared with three methods widely applied in different aquifers around the world (AVI, GOD and DRASTIC). Comparisons with these methods and validation tools (hydrogeological data and tracer test) show the advantages of the COP method in the assessment of vulnerability of karstic groundwaters.
Keywords: VULNERABILITY MAPPING; CARBONATE AQUIFERS; KARST; COP METHOD; SOUTHERN SPAIN